MILITARY ALLIANCES: CATALYSTS FOR WAR OR ARCHITECTS OF PEACE? A RETROSPECTIVE ANALYSIS OF THE RUSSO-UKRAINIAN CONFLICT, 2014–2025 - Mahakwe, ANYALEBECHI, Shammah; Allen, Akogu (Journal of Learning on History and Social Sciences, 2025)
Objective: This study investigates the role of military alliances, particularly NATO, in influencing the escalation and regional security dynamics of the Russo-Ukrainian conflict from 2014 to 2025, aiming to determine whether such alliances function as deterrents or catalysts of hostilities. Method: Employing a qualitative research design grounded in neorealist theory, the study conducted content analysis of diplomatic documents, official statements, and media reports to examine perceptions and actions surrounding the conflict. Results: Findings indicate that NATO’s eastward expansion and Russia’s perception of strategic encirclement significantly contributed to heightened tensions, illustrating the dual nature of military alliances as both stabilizing forces and provocateurs in international relations. Novelty: This research advances understanding by critically highlighting the paradoxical impact of military alliances in modern conflict, emphasizing that while alliances may bolster security, they can also inadvertently escalate conflicts when perceived as existential threats. The study underscores the necessity for transparent diplomatic communication and confidence-building measures to mitigate security dilemmas inherent in alliance politics, offering valuable insights for policymakers engaged in conflict prevention and regional stability.